Application Design For Palm Oil Ramp Search in North Bengkulu Web Based GIS - Agib Kristian Herianto; Anisya Sonita; Muntahanah Muntahanah; Yulia Darnita (Jurnal Komputer, Informasi dan Teknologi, 2023)
The development of the world of oil palm plantations in the Bengkulu region is growing very rapidly and one of them is the North Bengkulu district. With the increasing number of oil palm plantations, most people do not know where to sell the products from their oil palm plantations. The lack of available information and the unclear distance to the location makes it difficult for farmers to sell the products from their plantations. This research is aimed at solving problems by creating new applications. a smartphone (Android) based application which aims to provide solutions to the public so that they can easily find out where they are and how far they have to go to reach the oil palm road they want without being limited by time or place. GIS-based applications have been proven to have a major impact on economic and social development, and the use of GIS has become a current trend. The GIS application was developed to help search for and locate oil palm RAMPs. The aim of this research is to help oil palm farmers find and determine the best locations to sell their crops. They can also compare the selling prices of the most expensive palm oil. For this application, the Android operating system is combined with Google Maps, a web-based virtual world map service created by Google. This application has features such as the name of the palm ramp owner, a map of the palm ramp location, palm oil prices, location suggestions, palm oil views, application instructions, and much.